Impacts of ferric chloride, ferrous chloride and solid retention time on the methane-producing and physicochemical characterization in high-solids sludge anaerobic digestion. (August 2019) - Qin, Yujie; Chen, Linyi; Wang, Tongyu; Ren, Junyi; Cao, Yan; Zhou, Shaoqi
Abstract: This study used a batch experiment and a long-term experiment to investigate the effects of FeCl3 and FeCl2 on the high-solids anaerobic digestion (HSAD) of sludge for improving the methane productions. The results of batch experiment with an organic loading rate of 6.93 gVS/L suggested that the cumulative methane productions were enhanced by 28.9% and 6.4% with 200 mg/L FeCl3 and 250 mg/L FeCl2 in HSAD system, respectively. The higher methane productions were also obtained by 200 mg/L FeCl3 and 250 mg/L FeCl2 in the long-term experiment for 114d. An excessive FeCl3 could inhibit the HSAD process, which would be gradually recovered by the ammonia and the microbes acclimated to this environment. The organics degradation results indicated that the addition of 200 mg/L FeCl3 or 250 mg/L FeCl2 could show a positive effect on the substrate environment of a stable total volatile fatty acids (TVFA) concentration and pH, and promote the protease and dehydrogenase activities in HSAD system. In addition, the SRT played a significant role in the HSAD process by balancing hydrolysis-acidification and methanogenesis. An appropriate dosage of FeCl3 and FeCl2 improved the methane productions, and blocked the accumulation of TVFA caused by shortening SRT. Highlights: We comparatively studied the effects of FeCl3 and FeCl2 in sludge HSAD system. The best concentrations of FeCl3 and FeCl2 were 200 mg/L and 250 mg/L. FeCl3 and FeCl2 created positive environment and promoted enzymatic activities. Excessive FeCl3 exhibited a more serious inhibition effect than excessive FeCl2 . SRT played a significant role in sludge HSAD system.